The Contribution of Syeikh H. M. Arsyad Thalib Lubis to the Development of Islamic Education in Indonesia - Bagus Sanjaya; Danny Abrianto (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
Islamic education in Indonesia is now facing serious challenges in the form of moral crisis, spiritual degradation, and dichotomy between knowledge and values. This condition demands the revitalization of an educational paradigm that is able to unite intellectual, ethical, and spiritual aspects. This research aims to examine the contribution of Sheikh H. M. Arsyad Thalib Lubis in the development of Islamic education through his ideas, intellectual works, and institutional work. The research employs a qualitative approach with a character study method. Primary data were obtained through interviews with educational figures who understood his work, while secondary data were sourced from written documents, scientific works, archives, and historical publications. Data collection techniques include observation, interviews, and documentation, which are then analyzed descriptively-analytically to examine his thoughts, principles, and social influence in the context of education. The results showed that Sheikh Arsyad Thalib Lubis' integrative education paradigm rejects the dichotomy of religious and general sciences, emphasizes the balance between mind and heart, and places education as a means of forming knowledgeable, moral, and socially responsible humans. His thinking is relevant to be applied as a solution to the challenges of globalization and secularization in contemporary Islamic education.